Development of a Scrapbook-Based Basic Pop-Up Model as a Learning Medium to Enhance Creative Thinking Skills in IPAS Instruction - Nurfiyaturrizkiah, Siti; Alwi, Mijahamuddin; Hakim, Arif Rahman; Kudsiah, Musabihatul (FONDATIA, 2025)
This study addresses the gap in research on interactive scrapbook media, despite its demonstrated potential to enhance creative thinking in primary school science education. The objective is to develop and evaluate the ScrapBook Basic Pop-Up media to improve the creative thinking skills of fourth-grade students at SDN 1 Rumbuk within the IPAS curriculum. Employing a Research and Development (R&D) methodology based on the ADDIE model, the study involved 47 purposively selected students, divided into experimental and control groups. Data collection methods included structured observation sheets, expert validation questionnaires, teacher and student practicality questionnaires, and creative thinking tests focusing on fluency, flexibility, originality, and elaboration. Data were analyzed through quantitative techniques, such as N-Gain and t-tests as well as qualitative descriptive analysis. The findings indicate that the ScrapBook Basic Pop-Up media is valid, practical, and effective in enhancing creative thinking. Significant improvements were observed in post-test scores for all assessed indicators (N-Gain = 0.70, high category), alongside high levels of student participation, motivation, and engagement (87–92%). Expert validation affirmed the accuracy of content and quality of design, while teacher and student feedback emphasized the media’s usability, appeal, and ability to support concrete understanding. These results are consistent with existing literature on the role of scrapbook and pop-up media in fostering active learning and creativity. The study concludes that ScrapBook Basic Pop-Up media effectively promotes creative thinking and active engagement in IPAS learning, offering practical insights for educators and a foundation for future research on digital media integration and long-term educational impacts.